Quels territoires pertinents pour écologiser les industries qui misent sur le renouvelable ? - Gabrielle Bouleau; Caitríona Carter; Arnaud Sergent; Yann Fournis (Développement Durable et Territoires)
Renewables’ industries position themselves at the heart of ecological transition strategies to justify their territorial insertion. This has not, however, protected them from criticism on grounds of sustainability. Indeed, the government of these industries has come under attack, with opponents saying that industry actors have failed to address critical interdependencies necessary for sustainability to be achieved, including territorial ones. In this context, this article questions the functional argument of “spatial fit”, used by some analysts of ecological transition to explain the choice of regulatory scale. We do this by examining how actors use territorial resources to politicize the environmental government of these industries. Three case-studies are compared: salmon in Scotland, wind power in Quebec and wood energy in France. We show that the “spatial fit”, argument neither explains governing choices nor is sufficient for actors seeking to build legitimate regulation.